Global payment disruptions and firm-level exports - Ralphcde Haas; Karolin Kirschenmann; Alison Schultz (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
We exploit proprietary information on severed correspondent banking relationships - due to the stricter enforcement of financial crime regulation - to assess how payment disruptions impede cross-border trade. Using firm-level export data from emerging Europe, we show that when local respondent banks lose access to correspondent banking services, their corporate borrowers start to export less. This trade decline occurs on both the extensive and intensive margins and firms do not substitute foregone exports with higher domestic sales. As a result, total firm revenues and employment shrink. These findings highlight an often overlooked function of global banks: providing the payment infrastructure that enables firms in less-developed countries to export to richer parts of the world.
Keywords: F14; F15; F36; G21; G28; 330; Correspondent banking; payment infrastructure; global banks; international trade; anti-money laundering